Sr(3)Co(2)O(4.33)h(0.84): an extended transition metal oxide-hydride. - Helps, R; Rees, N; Hayward, M (2010)
Reaction of the n = 2 Ruddlesden-Popper oxide Sr(3)Co(2)O(5.80) with CaH(2) yields an extended oxide-hydride phase: Sr(3)Co(2)O(4.33)H(0.84). Neutron powder diffraction data reveal the material adopts a body-centered orthorhombic structure (Immm: a = 3.7551(5) Å, b = 3.7048(4) Å, c = 21.480(3) Å) in which the hydride ions are accommodated within disordered CoO(1.16)H(0.46) layers. Low temperature neutron powder diffraction data show no evidence for long-range magnetic order, suggesting the chemical disorder in the anion lattice of the material leads to magnetic frustration.